PENGARUH PRODUKSI, KONSUMSI DAN EKSPOR KOPI TERHADAP PDB SUBSEKTOR PERKEBUNAN DI INDONESIA - Muhammad Yusril Alfareza; Ichsan Ichsan (LPPM Universitas Malikussaleh - Indonesia, 2024)
This research aims to determine the effect of coffee production, coffee consumption and coffee export on GDP in the plantation subsector in Indonesia. This research use time series data from 1993 to 2022 with the Autoregressive Distributed Lag (ARDL) method. The results of data analysis based on the ARDL model show that coffee production in the short term has a positive and significant effect on GDP in the plantation subsector, but in the long term coffee production has a negative and significant effect on GDP in the plantation subsector. The coffee consumption in the short term and long term has a positive and significant effect, and the coffee export in the short term has a positive and significant effect, but in the long term coffee export has negative and significant effect. it is hoped that the development coffee will continue to be improved, so that the quality of Indonesian coffee is better well be to compete with coffee from other countries and make a major contribution to GDP in the plantation subsector in the future